Complete mitochondrial genomes of three skippers in the tribe Aeromachini (Lepidoptera: Hesperiidae: Hesperiinae) and their phylogenetic implications. Issue 12 (18th May 2021) - Hao, Xiangyu; Liu, Jiaqi; Chiba, Hideyuki; Xiao, Jintian; Yuan, Xiangqun
Abstract: The mitochondrial genome is now widely used in the study of phylogenetics and molecular evolution due to its maternal inheritance, fast evolutionary rate, and highly conserved gene content. To explore the phylogenetic relationships of the tribe Aeromachini within the subfamily Hesperiinae at the mitochondrial genomic level, we sequenced and annotated the complete mitogenomes of 3 skippers: Ampittia virgata, Halpe nephele, and Onryza maga (new mitogenomes for 2 genera) with a total length of 15, 333 bp, 15, 291 bp, and 15, 381 bp, respectively. The mitogenomes all contain 13 protein‐coding genes (PCGs), 22 transfer RNAs (tRNAs), 2 ribosomal RNAs (rRNAs), and a noncoding A + T‐rich region and are consistent with other lepidopterans in gene order and type. In addition, we reconstructed the phylogenetic trees of Hesperiinae using maximum likelihood (ML) and Bayesian inference (BI) methods based on mitogenomic data. Results show that the tribe Aeromachini in this study robustly constitute a monophyletic group in the subfamily Hesperiinae, with the relationships Coeliadinae + (Euschemoninae + (Pyrginae + ((Eudaminae + Tagiadinae) + (Heteropterinae + ((Trapezitinae + Barcinae) + Hesperiinae))))). Moreover, our study supports the view that Apostictopterus fuliginosus and Barca bicolor should be placed out of the subfamily Hesperiinae. Abstract : To explore the phylogenetic relationships of the tribe Aeromachini within the subfamily Hesperiinae at the mitochondrial genomics level, we sequenced and annotated the complete mitogenomes of three skippers: Ampittia virgata, Halpe nephele, and Onryza maga . Results show that the 3 Aeromachini species in this study robustly constitute a monophyletic group in the subfamily Hesperiinae, with the relationships Coeliadinae + (Euschemoninae + (Pyrginae + ((Eudaminae + Tagiadinae) + (Heteropterinae + ((Trapezitinae + Barcinae) + Hesperiinae))))). Moreover, our study supports the view that Apostictopterus fuliginosus and Barca bicolor should be placed out of the subfamily Hesperiinae.